2013
DOI: 10.1007/s10456-013-9394-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-320 regulates tumor angiogenesis driven by vascular endothelial cells in oral cancer by silencing neuropilin 1

Abstract: Tumor angiogenesis is a critical process during cancer progression that modulates tumor growth and metastasis. Here, we identified an anti-angiogenic microRNA, miR-320, which is decreased in oral squamous cell carcinoma (OSCC) cell lines and tumor tissues from OSCC patients, down-regulated in blood vessels and inversely correlated with vascularity in OSCC tissues. Neuropilin 1 (NRP1), an important regulator of angiogenesis, was found to be a target of miR-320. The 3'-untranslated region of NRP1 mRNA contains m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 49 publications
3
93
0
Order By: Relevance
“…Various miRNA have been implicated in the invasion, metastasis, and maturation of several types of cancer, including RB (7)(8)(9)(10). miR-320 has been demonstrated to be involved in various types of cancer, including colorectal cancer (11), non-small cell lung cancer (12), cervical cancer (13), and oral cancer (14). In a previous miRNA microarray analysis, miR-320 was identified to be associated with the tumorigenesis of RB for the first time, indicating that miR-320 has a role in the regulation of RB development (15).…”
Section: Introductionmentioning
confidence: 99%
“…Various miRNA have been implicated in the invasion, metastasis, and maturation of several types of cancer, including RB (7)(8)(9)(10). miR-320 has been demonstrated to be involved in various types of cancer, including colorectal cancer (11), non-small cell lung cancer (12), cervical cancer (13), and oral cancer (14). In a previous miRNA microarray analysis, miR-320 was identified to be associated with the tumorigenesis of RB for the first time, indicating that miR-320 has a role in the regulation of RB development (15).…”
Section: Introductionmentioning
confidence: 99%
“…miR-320a regulates glycolysis and represses angiogenic factors, including Flk1, VEGFc, insulin-like growth factor 1, insulin-like growth factor 1 receptor, and fibroblast growth factor (28,29). miR-320a has also been implicated in tumor angiogenesis by silencing NRP1 (30). miR-27b is thought to promote angiogenesis by targeting antiangiogenic genes (31), including the transmembrane protein SEMA6A.…”
Section: Mechanistic Links To Angiogenesismentioning
confidence: 99%
“…Furthermore, Wu et al (28) demonstrated that miR-320, which was decreased in oral squamous cell carcinoma tissues and cell lines, suppressed the tumorigenicity of oral squamous cell carcinoma cells in vitro and tumor angiogenesis in vivo, via inhibition of neuropilin 1. In addition, Wu et al (28) reported that miR-320 was downregulated in prostate cancer, and that the upregulation of miR-320 inhibited carcinogenesis and progression of prostate cancer through the downregulation of the Wnt/β-catenin signaling pathway. The overexpression of miR-320 in prostate stem-like tumor-initiating cells marke dly inhibited the stem cell-like properties of prostate cancer cells, including tumorsphere formation, chemoresistance and tumorigenic abilities (29).…”
Section: Discussionmentioning
confidence: 99%